Reducing Complaints of Itching for the Comfort of Pruritic Elderly With Garra Rufa Care Breathing Relaxation (Gc-Br) Based on Kolcaba's Comfort Nursing Theory - Wimar Anugrah Romadhon; Ita Noviasari (Indonesian Journal of Global Health Research, 2023)
Coronavirus Disease 2019 can cause systemic infections that significantly affect the immune response and hemostatic conditions. A biomarker is needed to predict patients in the severity of the disease or severe complications or when doing triage upon admission to the hospital, providing early intervention, so as to reduce mortality. Changes in levels of lymphocytes, neutrophils, leukocytes can predict the risk of worsening Covid-19 patients. The purpose of this study was to determine the effect of lymphocytes, neutrophils and leukocytes on the outcome of Covid-19 patients at Haji Adam Malik General Hospital Medan. This study uses an observational analytic design with a retrospective approach. The population of this research is medical records of Covid-19 confirmed positive by real-time Polymerase chain reaction (rt-PCR) from the Laboratory of Haji Adam Malik General Hospital Medan for the period January-December 2021. Sampling using purposive sampling as many as 175 medical records. The test used to determine the relationship of lymphocytes, neutrophils and leukocytes to the outcome of Covid-19 patients is the Spearman correlation test. The results showed that there was a weak and positive relationship between lymphocytes (p = 0.006; r = 0.208) and the outcome of Covid 19 patients, there was a moderate and positive relationship between neutrophils (p = 0.000; r = 0.276) and the outcome of Covid 19 patients. moderate and positive relationship between leukocytes (p = 0.000; r = 0.350) and the outcome of Covid 19 patients. It is recommended to conduct a study in a large group by comparing the severity of the disease and the length of stay.